2011
DOI: 10.1590/s1807-59322011000900018
|View full text |Cite
|
Sign up to set email alerts
|

High-energy extracorporeal shockwave therapy in a patellar tendon animal model: a vascularization-focused study

Abstract: OBJECTIVE:The aim of this study was to analyze the effect of high-energy extracorporeal shockwave therapy on tendon angiogenesis in the patellar tendons of rabbits. We sought to investigate whether different voltage and number pulses modify the angiogenesis pattern.INTRODUCTION:High-energy extracorporeal shockwave therapy is an option in the treatment of orthopedic diseases such as chronic tendonitis. Despite its potential clinical applicability, there have been few studies on this technique that examine both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…No alteration of normal cancellous bone architecture was reported (23). By contrast, a study on normal insertional patellar tendon (rabbit) indicated no alteration in the number of capillaries at 6 weeks after one session of different ESWT regimens (1,000 or 2,000 pulses, 0.18, 0.27 or 0.36 mJ/mm 2 ) (19).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…No alteration of normal cancellous bone architecture was reported (23). By contrast, a study on normal insertional patellar tendon (rabbit) indicated no alteration in the number of capillaries at 6 weeks after one session of different ESWT regimens (1,000 or 2,000 pulses, 0.18, 0.27 or 0.36 mJ/mm 2 ) (19).…”
Section: Resultsmentioning
confidence: 98%
“…According to the subjects, studies in the literature were able to be classified as in vivo or in vitro studies. In vivo studies had been performed on rats [6 papers (10-15)], rabbits [5 papers (6,16-19)], horses [one paper (20)], ponies [2 papers (21,22)] and dogs [one paper (23)], an on normal tendons [9 papers (6,12,14,16,17,19,(21)(22)(23)] and diseased tendons [6 papers (10,11,13,18,20,24)]. The experimental model for diseased tendons was either a ruptured tendon, in the form of a complete and sutured rupture or a partial rupture [2 papers (10,13)] or a collagenase-induced tendinopathy [4 papers (11,15,18,20)].…”
Section: Resultsmentioning
confidence: 99%
“…Laser, light emitting diode, radiofrequency ablation, hyperbaric oxygen and autologous tenocyte therapies have all shown some promise with respect to improving the mechanical or histological properties of healing tendon, 126-128 while the beneficial effects of high-energy extracorporeal shockwave therapy have not shown as much benefit in tendon repair as in the treatment of other musculoskeletal disorders. 129-131 In general, the goal is to improve the quality of tendon tissue after injury and allow earlier and more aggressive rehabilitation protocols to speed recovery.…”
Section: Patellamentioning
confidence: 99%
“…The posterolateral capsule was important for varus stability and for external rotation stability in extension. Using a rabbit animal model, Penteado et al 10 analyzed the effect of high-energy extracorporeal shockwave therapy on tendon angiogenesis in the patellar tendons of rabbits, investigating whether different voltages and number pulses modify the angiogenesis pattern. High-energy extracorporeal shockwave therapy was applied at the tibial insertion of the left patellar ligament in 30 rabbits that were separated into six groups that differed in terms of the voltage and number of applied pulses.…”
Section: General Reviewmentioning
confidence: 99%